Comparison of drought tolerance among winter wheat hybrids and their parents using a comprehensive screening method - Filbert, Seth Alan (Kansas State University, 2017)
Drought is known to be one of the most limiting abiotic stresses for wheat (Triticum aestivum L.) production, not only in the Midwest, but throughout the world. It is a complex issue and one that is difficult to screen for when breeding for new varieties. Hybrid wheat is one possible tool for breeders to use in order to make genetic gains towards better tolerance. The effectiveness of hybrid wheat as a tool to address regular periods of drought is a topic of continual discussion. The purpose of this study was to perform a comprehensive screening for drought tolerance comparing two different experimental hybrid entries to their parents. The hybrids were selected based on their good performance under drought in prior field trials. Plants were grown in PVC columns containing sensors that monitored growth media water content and matric potential. All plants were grown equally until heading. Drought treatment began 10 days post anthesis. Plants were observed until senescence/maturity. Several different agronomic characteristics were measured along with physiological traits that have previously been linked to drought tolerance. After completion of the screening, it was observed that the hybrid entries tended to fall between the two parents for a majority of the measurements. When comparing the hybrids to the parents overall, at least one parent outperformed its hybrid in every category. Parent line Parent B was one of the highest ranking genotypes for all measurements. Different drought mechanisms were observed across genotypes upon completion of the treatment. Further research is necessary to understand the hybrid response to drought when compared to pure line varieties.
Keywords: Hybrid wheat; Drought tolerance; Wheat breeding; ScreeningWheat